O processo de formação de educadores na gestão de Paulo Freire: história de disputas na Secretaria Municipal de Educação (1989-1992) - Souza, Angélica Riello de (2023)
This is an investigation into the training process of educators from the municipal education network under the management of Paulo Freire, between 1989 and 1992. For this purpose, sources produced by the Municipal Departament of Education related to the theme were selected, considering the proposal of Popular Public Education course at that time, synthesized in the document entitled Common Rules of Municipal Schools, definitively enacted in December 1992, dependent on the functioning of school councils, whose popular participation was motivated by the efforts of the Workers' Party administration. Teachers' testimonies collected by Torres were also analyzed; O'Cadiz; Wong (2003), in a sociological research process, between 1989 and 1994, to register the implementation of the curriculum through interdisciplinarity in the SME and in the school units. The objective was to analyze the Secretariat's proposals for the training of municipal educators, considering them the main interlocutors of the proposal, in order to verify the permanence of previous conceptions, proposed transformations, the resistance of the subjects, and the construction of the popular democratic school. The documents produced by the Municipal Secretary of Education were analyzed from the concept of the statement, mobilized by Mikail Bakhtin and Valentin Voloshinov, revealing an attempt to spread new conceptions and visions in the municipal education system, through the elaboration of a speech progressive political-pedagogical, whose objective was to promote the reform that aimed to combat banking, authoritarian and elitist pedagogical practices, according to the discursive formulation that composed an official ideology. The reports of teachers' experiences in implementing the popular education proposal, recorded in the research of Carlos Torres, Pilar O'Cadiz, and Pia Wong, were considered as responsive utterances, whose concreteness is understood as an action in a dialogic discourse analysis, to highlight everyday ideology. The dynamics between the ideologies showed a process of disputes and tensions, understood as the subjects' actions to guarantee the material survival of their lives and ideas, beyond the issue of ideological coherence. It was noted the difficulty of implementing the proposal that fought pedagogies classified as traditional as a conception of pedagogical practice, but that was rooted in the practice of educators who, through a proposal that demanded commitment of their time, constructed an argument that pointed to a tendency to seek to follow models that are stricter and closer to traditional pedagogy. Such actions were interpreted from the concept of experience, by the English historian Edward Thompson, in addition to revealing the multifactoriality and multimodality that make up the history of educational institutions, as pointed out by historian Justino Magalhães